PENIDIDKAN KARAKTER DALAM KELUARGA - Satriah, Lilis (IAIN Ponorogo, 2011)
Character education implemented at the school recently will run well if it is supported by character education at home. It can not be denied that the percentage of the pupilsâ activity learning at school is only about 10% to 15% less than that of their activities at home. As a result of this case, the implementation of character building by teachers at school is obviusly limited when it is compared with the educational policies adopted by the parents at home. To make the matter worse, it might be possible that the character education built by teachers in the classroom is able to be broken down by the parents attitudes abusive to the pupils at home. To fill this void, therefore, the application of character education in the family is one of golden ways to anticipate the occurrence of various problems that occur in the community life. By implementing character education in the family, it means that the parents have prepared their children who have good character and morals and become heir to the cadres and leaders of the nations in the future. Thus, the essential thing to note is that how the parents realize the importance of good and proper parenting, in so doing, they will have self-awareness to suit their parenting styles that best fit to their children needs and wants, and always try to improve their insight and knowledge about parental system.ÙØ§ØªÙØ¬Ø Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø¥ÙØ§ Ø¨Ø¯Ø¹Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ Ø§ÙÙØ§ÙØ¯Ø§Ù ÙÙ Ø§ÙØ¨ÙØª. ÙØ£Ù Ø§ÙØ·Ø§ÙØ¨ ÙØ¶Ù Ø£ÙØ«Ø± Ø£ÙÙØ§ØªÙ ÙÙ Ø§ÙØ¨ÙØªØ ÙÙÙØ¶Ù ÙÙØ· 10 â 15 ÙÙ Ø§ÙÙ Ø¦Ø© Ù Ù Ø£ÙÙØ§ØªÙ ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø©. ÙØ¨ÙØ°Ø§ Ø ØªØ·Ø¨ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø£ÙÙ ÙØ¯Ø±Ø§ Ø¨Ø§ÙÙØ³Ø¨Ø© ÙÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ Ø§ÙÙØ§ÙØ¯Ø§Ù ÙÙ Ø§ÙØ£Ø³Ø±Ø©. ÙÙØ¯ ØªÙØ³Ø¯ ÙØªØ§Ø¦Ø¬ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø¨Ø³ÙØ¡ Ø§ÙØªØµØ±ÙØ§Øª ÙØÙÙ Ù Ù ÙØ¨Ù Ø§ÙÙØ§ÙØ¯ÙÙ.Â ÙØ¨ÙØ°Ø§ ÙØ§ÙØª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙÙ Ø§ÙØ£Ø³Ø±Ø© Ø¹ÙØµØ±Ø§ ÙØ§Ù Ø§ ÙÙ Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙØ·Ø§ÙØ¨ ÙÙ ÙØ§Ø¬ÙØ© Ø§ÙÙ Ø´ÙÙØ§Øª ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹. ÙÙÙ ÙØ°Ø§ ÙØ¯ Ø£Ø¹Ø¯Øª Ø§ÙØ£Ø³Ø±Ø© Ø´Ø¨Ø§ÙØ§ Ù ØªØ®ÙÙÙÙ Ø¨Ø£Ø®ÙØ§Ù ÙØ±ÙÙ Ø© Ø§ÙØ°ÙÙ â ÙÙ Ø§ÙÙ Ø³ØªÙØ¨Ù -Â Ø³ÙÙÙÙÙÙ Ø±Ø¤Ø³Ø§Ø¡ ÙØ±Ø¬Ø§ÙØ§ . Ø§ÙØ£Ù ÙØ± Ø§ÙØªÙ ÙØ§Ø¨Ø¯ Ø£Ù ÙÙØªØ¨Ù Ø¥ÙÙÙØ§ Ø§ÙØ¢Ø¨Ø§Ø¡ ÙØ§ÙØ£Ù ÙØ§Øª ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙÙ Ø§ÙØ£Ø³Ø±Ø©Ø ØÙØ« ÙØØ§ÙÙ Ø§ÙÙØ§ÙØ¯Ø§Ù ÙÙ ØªØØ³ÙÙ Ø£Ø¯Ø§Ø¦ÙØ§ ÙØ§ÙØªØ²ÙØ¯ Ø¨Ø§ÙÙ Ø¹Ø§Ø±Ù ÙØ§ÙØ¹ÙÙÙ Ø¹Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØµØÙØØ©.